Clinical features, neurologic recovery, and risk factors of postoperative posterior fossa syndrome and delayed recovery: a prospective study. Issue 9 (5th April 2021) - Khan, Raja B; Patay, Zoltan; Klimo, Paul; Huang, Jie; Kumar, Rahul; Boop, Frederick A; Raches, Darcy; Conklin, Heather M; Sharma, Richa; Simmons, Andrea; Sadighi, Zsila S; Onar-Thomas, Arzu; et al.
Abstract: Background: Posterior fossa syndrome (PFS) is a known consequence of medulloblastoma resection. Our aim was to clinically define PFS, its evolution over time, and ascertain risk factors for its development and poor recovery. Methods: Children with medulloblastoma treated at St Jude Children's Research Hospital from 6/2013 to 7/2019 received standardized neurological examinations, before and periodically after radiation therapy. Most (98.3%) were enrolled on the ongoing multi-institutional protocol (SJMB12; NCT 01878617). Results: Sixty (34%) of 178 evaluated children had PFS. Forty (23%) had complete mutism (PFS1) and 20 (11%) had diminished speech (PFS2). All children with PFS had severe ataxia and 42.5% of PFS1 had movement disorders. By multivariable analysis, younger age ( P = .0005) and surgery in a low-volume surgery center ( P = .0146) increased PFS risk, while Sonic Hedgehog tumors had reduced risk ( P = .0025). Speech and gait returned in PFS1/PFS2 children at a median of 2.3/0.7 and 2.1/1.5 months, respectively, however, 12 (44.4%) of 27 PFS1 children with 12 months of follow-up were nonambulatory at 1 year. Movement disorder ( P = .037) and high ataxia score ( P < .0001) were associated with delayed speech recovery. Older age ( P = .0147) and high ataxia score ( P < .0001) were associated with delayed gait return. Symptoms improved in all children but no child with PFS had normal neurologic examination at a median of 23 months after surgery. Conclusions: Categorizing PFS into types 1 and 2 has prognostic relevance. Almost half of the children with PFS1 with 12-month follow-up were nonambulatory. Surgical experience was a major modifiable contributor to the development of PFS.